Rung Ho! A Novel - Mundy, Talbot, 1879-1940 (Salt Lake City, UT : Project Gutenberg, 2004)
"Rung Ho! A Novel" by Talbot Mundy is a work of fiction written in the early 20th century. The story is set against the backdrop of colonial India, where it follows the journey of a spirited young woman named Rosemary McClean, who is determined to help her father in his mission against the oppression faced by the local populace. As she navigates the dangerous streets of Howrah City, she encounters various characters, including a menacing prince and a complex warrior named Mahommed Gunga, all amidst the tensions brewing in the region. At the start of the novel, Rosemary is seen riding through a bustling bazaar, unaccompanied by anyone except for an old woman from the sweeper caste, who can't provide her much protection. The atmosphere in Howrah is rife with unrest, as both natives and foreign rulers grapple with power dynamics. As Rosemary stands her ground against an aggressive pursuer, Jaimihr, the prince, the narrative delves into themes of courage, rebellion, and the turbulent interplay of colonialism. Concurrently, Mahommed Gunga is introduced as a proud figure, involved in plotting against the British who occupy India and holding a deep respect for Rosemary's resolve. The early chapters set the stage for a gripping tale filled with political intrigue, cultural conflicts, and personal bravery as the characters confront the complex realities of their world. (This is an automatically generated summary.)
Release date is 2004-02-01
Produced by M.R.J., and David Widger
Keywords: India -- Fiction